A combined coagulation–ultrafiltration method for enhanced separation of proteins and polyphenols. Issue 6 (12th April 2016) - Yu, X.; Bogaert, L.; Hu, R.; Bals, O.; Grimi, N.; Vorobiev, E.
ABSTRACT: This work aimed to separate proteins and polyphenols from rapeseed stem extracts. The results showed that coagulation with 40% w/w ethanol and ultra-filtration with 10 kDa membrane were two efficient methods for polyphenols purification. The purity of polyphenols increased from 80.3% to 97.0% after separation. The combination of ethanol coagulation with ultrafiltration permitted decreased the ethanol consumption from 40% to 10% w/w while maintaining high polyphenols purity. Significant protein loss at room temperature was observed during the stability test, which emphasizes the importance of elaborating a fast and effective separation method for rapeseed stem extracts.